Anti-inflammatory properties of Melaleuca quinquenervia (Cav.) ST Blake Myrtaceae (Niaouli) leaves’ essential oil - ACHA, Emile; AHOUNOU AÏKPE, FIFAMIN JUDITH; ADOVELANDE, JACQUES; ASSOGBA, M Fidèle; AGOSSOU, Essé; SEZAN, ALPHONSE (My University, 2019)
Melaleuca quinquenervia is a plant well-known for its medicinal properties. Its leaves are mainly used for the treatment of respiratory diseases. The present study aims was to appreciate the anti-inflammatory properties of the essential oil from the leaves of Melaleuca quinquenervia (Cav.) ST Blake Myrtaceae (Niaouli). Phytochemical analysis of the essential oil, by CG/MS, revealed the major constituents such as: 1,8-cineole (30.14%), viridiflorol (29.92%), terpinene-4-ol (10.12%) α-terpineol (6.89%), limonene (4.36%). The study of the anti-inflammatory activity of this essential oil on wistar rats showed a decrease in the rate of the oedema evolution and displayed significant dose and time dependent of this oedema inhibition. The essential oil showed also strong analgesic and antipyretic properties. The dose of 1800 mg/kg showed a better activity than that induced by 50 mg/kg of acetylsalicylate of lysine. Altogether, this work demonstrates the anti-inflammatory property of Melaleuca quinquinervia leaves’ essential oil suggesting its potential role as adjuvant therapeutic alternatives in dealing with inflammatory-related and respiratory diseases.
Keywords: Essential oil; Melaleuca quinquenervia; anti-inflammation; Wistar rats.